(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
The article covers issues of pedagogical diagnostics, which is an integral component of pedagogical activity. It contains indicators for diagnosing the level of education of students.